2020
DOI: 10.35971/gojhes.v2i2.5270
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Faktor Resiko Kejadian Obesitas Pada Remaja Di Kota Gorontalo

Abstract: ABSTRAK Menurut World Health Organization (WHO) 2006, secara global terdapat lebih dari satu milyar penduduk dewasa yang kelebihan berat badan (gemuk), 300 juta diantaranya kegemukan (obes). Sejak tahun 1980 dibeberapa wilayah di Amerika Utara, Inggris, Eropa Timur, Timur Tengah, Kepulauan Pasifik, Australia dan Cina, jumlah penduduk yang menderita kegemukan berlipat tiga kali. Sebuah penelitian terbaru yang dipublikasikan dalam American Journal of Epidemiology, mengungkapkan, obesitas yang dialami seseorang p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
0
0
1
Order By: Relevance
“…The finding of the study showed that there was a significant relationship between the consumption of fast food and obesity incidents. It is also reinforced by the research of Setyaningsih which showed that consumption of snacks and other small foods in excess are factors that contributes the obesity in children [26], [27].…”
Section: Fast Food Consumptionmentioning
confidence: 94%
“…The finding of the study showed that there was a significant relationship between the consumption of fast food and obesity incidents. It is also reinforced by the research of Setyaningsih which showed that consumption of snacks and other small foods in excess are factors that contributes the obesity in children [26], [27].…”
Section: Fast Food Consumptionmentioning
confidence: 94%
“…Overweight has consequences for serious public health problems such as an increased risk of Non Communicable disease (NCDs) (6) (7).…”
Section: Introductionmentioning
confidence: 99%
“…Zaman sekarang, remaja banyak yang mengkonsumsi makanan fast food, makanan instan, dan minuman yang tinggi gula, kalori dibandingkan mengkonsumsi sayur dan buah (12) .…”
unclassified